Relative volume constraints for single view 3D reconstruction - Toeppe, Eno; Nieuwenhuis, Claudia; Cremers, Daniel (Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 2013)
We introduce the concept of relative volume constraints in order to account for insufficient information in the reconstruction of 3D objects from a single image. The key idea is to formulate a variational reconstruction approach with shape priors in form of relative depth profiles or volume ratios relating object parts. Such shape priors can easily be derived either from a user sketch or from the object's shading profile in the image. They can handle textured or shadowed object regions by propagating information. We propose a convex relaxation of the constrained optimization problem which can be solved optimally in a few seconds on graphics hardware. In contrast to existing single view reconstruction algorithms, the proposed algorithm provides substantially more flexibility to recover shape details such as self-occlusions, dents and holes, which are not visible in the object silhouette. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 3D reconstruction; depth profile; shading; single view; volume